On Truncated of General Family of Baskakov –Type Operators - Mohammad , Ali J.; Hassan, A.K. (Iraqi Journal of Science, 2022)
Recently, in 2014 [1] the authors introduced a general family of summation integral Baskakov-type operators ( ) . In this paper, we investigate approximation properties of partial sums for this general family.